Mortality after release from incarceration in New Zealand by gender: A national record linkage study. (December 2022) - Cunningham, Ruth; King, Paula Toko; Telfer, Kendra; Crengle, Sue; Carr, Julia; Stanley, James; Gibb, Sheree; Robson, Bridget
Abstract: Background: People who enter and leave places of incarceration experience considerable health inequities and are at increased risk of premature death compared to the general population. Causes of premature death in this population vary markedly between countries and so country-specific information is needed. Additionally, there is a lack of large population-based studies which can disaggregate mortality risk based on person and incarceration factors. This study is the first examination of mortality in the period following release from incarceration in New Zealand. Methods: We linked deidentified administrative data on incarceration and release between 1 January 1998 and 31 December 2016 with national mortality data for the same period to examine mortality after release in those who had been incarcerated for at least 1 day. Age standardised mortality rates and mortality ratios compared to the general New Zealand population were calculated separately for men and women, for releases from remand compared with prison, and by cause of death and time since release. Results: 90, 195 individuals (13% women, 49% Māori) were followed up for 9.4 years after release from incarceration, with 4, 764 deaths over the follow-up period. The overall standardised mortality ratio was 3.3 (95% CI 3.2, 3.4) compared to the general population, and higher for women (3.8) than men (2.7). The most common causes of death were cardiovascular disease, cancer and suicide. Rates of death were similar following release from remand versus prison, however suicide rates were highest following release from remand. Regardless of the type of incarceration, mortality was highest in the first month after release. Conclusion: Experience of incarceration in New Zealand is associated with high rates of mortality from both chronic conditions and external causes. There are urgent policy imperatives to recognise and actively address the increased health and mortality risks faced by people released from New Zealand prisons. Highlights: People released from incarceration in NZ have more than three times the death rate of the general population. The relative impact of incarceration on mortality was greater for women than men. Chronic conditions are important causes of death after release from incarceration in NZ. The mortality risk from all causes is highest in the first month after release. Suicide rates were highest among those released from remand.